Post-Brexit Regionalism - Syarifah Nurma Afhiani; Syarif Redha Fachmi Al Qadrie; Ratu Zahirah Lutfie; Syarif Usmulyadi; Fuzy Firda Zhan; Elyta (Cita konsultindo, 2023)
British Exit (Brexit) is an issue that occurred after the British government's statement leaving the European Union. The main driving factor for British society to leave European Union membership is many waves of immigrants entering the UK. This study uses a research method with a qualitative approach in a causal way to show a reciprocal relationship. The research results show thatBrexitincluded in the regionalization group, which significantly impacted trade and political relations between the United Kingdom and other countries, including Indonesia. The negative impact of Brexit on the UK is that it will affect the economy, which threatens global growth, the decline in the value of stocks, and the money market in England is increasingly experiencing a crisis. At the same time, the impact of Brexit on Indonesia will make it difficult for Indonesia to export its production goods to Europe and a decline in the exchange rate of the Rupiah. On the other hand, Brexit will also positively impact Indonesia because the instability of global market conditions can provide opportunities for funds to enter Indonesia through tax amnesty.